TICT based fluorescent probe with excellent photostability for real-time and long-term imaging of lipid droplets. Issue 29 (18th July 2019) - Li, Yunxia; Zhang, Minjie; Chen, Xiaohui; Liang, Jianshu; Chen, Dongcheng; Gao, Meng; Ren, Li
Graphical abstract: Highlights: The probe has typical twisted intramolecular charge transfer characteristics. The probe is almost non-emissive in aqueous solution, but becomes highly emissive in the hydrophobic microenvironment. The probe has excellent photostability and high emission efficiency. The probe can be used for wash-free and long-term imaging of lipid droplets. Abstract: Lipid droplets (LDs) are dynamic organelles and involve in various physiological processes by regulation of the storage and metabolism of lipid molecules. The real-time and long-term imaging of LDs' distribution and movement is critical for investigation of their biological functions. However, current LDs-targeted fluorescent probes suffer from low photostability and high background noise. To tackle these challenges, we herein reported that the red-emissive fluorescent probe DCQTB with twisted intramolecular charge transfer (TICT) characteristics can be used for wash-free imaging of LDs with advantages of fast cell penetration ability, high specificity, excellent photostability, and low phototoxicity. This LDs-specific fluorescent probe is thus promising for investigation of the biological functions of LDs.